Optimalisasi Restorative Justice Sebagai Bentuk Perlindungan Hukum Terhadap Anak Yang Berhadapan Dengan Hukum di Polda Jambi - Irawan, Agus; Ternando, Albi; Kurniawan, Ridha (Legalitas: Jurnal Hukum, 2024)
Restorative Justice is expected to be one of the ways or alternatives to handle crimes or crimes that prioritize the restoration of the balance of the relationship between the perpetrator of the crime and the victim Protection for children who are facing the law is the prerogative of children. The research approach used in this study is the method This research is empirical legal research, The internal factor faced by the Jambi Police in the implementation of restorative justice for children is the lack of time given by law because of the law The invitation only gives a deadline of 30 days, the time is very short, considering that in summoning witnesses and victims it is also quite difficult because they are not necessarily present at the specified time, which hinders investigators in their examination efforts, and sub-directorate IV of the Renakta and the Vulnerable group room still lack skilled and educated investigator personnel in handling children's cases, there is only one investigator who has special expertise as a child investigator. External factors include the factor of the child who is dealing with the law of the child as the perpetrator who commits the crime in the examination still seems afraid to provide information related to the criminal act committed, the factor of the victim and the victim reporter and the complainant does not want to forgive the child who are facing the law and do not want to be resolved through restorative justice.